Association between exposure to arsenic, nickel, cadmium, selenium, and zinc and fasting blood glucose levels. (December 2019) - Li, Zhaoyang; Xu, Yali; Huang, Zhijun; Wei, Yue; Hou, Jian; Long, Tengfei; Wang, Fei; Hu, Hua; Duan, Yanying; Guo, Huan; Zhang, Xiaomin; Chen, Xiang; et al.
Abstract: Associations between single metal and fasting blood glucose (FBG) levels have been reported in previous studies. However, the association between multi-metals exposure and FBG level are little known. To assess the joints of arsenic (As), nickel (Ni), cadmium (Cd), selenium (Se), and zinc (Zn) co-exposure on FBG levels, Bayesian kernel machine regression (BKMR) statistical method was used to estimate the potential joint associations between As, Ni, Cd, Se, and Zn co-exposure and FBG levels among 1478 community-based Chinese adults from two counties, Shimen (n = 696) and Huayuan (n = 782), with different exposure profiles in Hunan province of China. The metals levels were measured in spot urine (As, Ni, and Cd) and plasma (Se and Zn) using inductively coupled plasma-mass spectrometry, respectively. The exposure levels of all the five metals were significantly higher in Shimen area (median: As = 57.76 μg/L, Cd = 2.75 μg/L, Ni = 2.73 μg/L, Se = 112.67 μg/L, Zn = 905.68 μg/L) than those in Huayuan area (As = 41.14 μg/L, Cd = 2.22 μg/L, Ni = 1.88 μg/L, Se = 65.59 μg/L, Zn = 819.18 μg/L). The BKMR analyses showed a significantly positive over-all effect of the five metals on FBG levels when metals concentrations were all above the 50th percentile while a statistically negative over-all effect when metals concentrations were all under the 50th percentile in Shimen area. However, a totally opposite over-all effect of the mixture of the five metals on FBG levels was found in Huayuan area. BKMR also revealed a non-linear exposure-effect of Zn on FBG levels in Huayuan area. In addition, interaction effects of As and Se on FBG level were observed. The relationship between single or combined metals exposure and FBG was different against different exposure profiles. Potential interaction effects of As and Se on FBG levels may exist. Graphical abstract: Image 1 Highlights: The associations between single or combined metals exposure and FBG levels were different against different exposure profiles. There was non-linear association of Zn with FBG levels in a relatively low metals exposure area. Potential interaction effects of As and Se on FBG levels may exist.